2011
DOI: 10.1093/brain/awr322
|View full text |Cite
|
Sign up to set email alerts
|

A rat model of Charcot–Marie–Tooth disease 1A recapitulates disease variability and supplies biomarkers of axonal loss in patients

Abstract: Charcot-Marie-Tooth disease is the most common inherited neuropathy and a duplication of the peripheral myelin protein 22 gene causes the most frequent subform Charcot-Marie-Tooth 1A. Patients develop a slowly progressive dysmyelinating and demyelinating peripheral neuropathy and distally pronounced muscle atrophy. The amount of axonal loss determines disease severity. Although patients share an identical monogenetic defect, the disease progression is strikingly variable and the impending disease course can no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 53 publications
4
55
1
2
Order By: Relevance
“…This was, to our knowledge, the first RNA-seq profiling of a CMT1A model, and the analysis showed some categories of genes in common with microarray profiles of other CMT1A models (34,37,38). For example, there was a significant decrease in cholesterol and lipid biosynthetic genes as well as myelin-related genes in 5-week-old C22 compared with WT littermates (Supplemental Figure 2, C and F).…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…This was, to our knowledge, the first RNA-seq profiling of a CMT1A model, and the analysis showed some categories of genes in common with microarray profiles of other CMT1A models (34,37,38). For example, there was a significant decrease in cholesterol and lipid biosynthetic genes as well as myelin-related genes in 5-week-old C22 compared with WT littermates (Supplemental Figure 2, C and F).…”
Section: Resultsmentioning
confidence: 65%
“…Thus, we also investigated ASO treatment in a second model, the heterozygous CMT1A rat (12,34,48), which contains 3 copies of a cosmid containing mouse Pmp22 and exhibits a milder demyelinating neuropathy than C22 mice. CMT1A rats exhibit grip-strength deficit starting at 5 weeks of age and significantly reduced CMAP and demyelination by 9 weeks of age (48). We performed in vitro screening with PBS for 9 weeks (Supplemental Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are mostly in animal models or cultured tissues. The initiating step in all of the above mechanism is a PMP22 toxic gain of function [18][19][20][21]25,27,33,47,49,51,52,65,67]. …”
Section: Diagnostic Featuresmentioning
confidence: 99%
“…Recently, in PMP22 transgenic rats, a German study demonstrated that transcriptional analysis of skin biopsy is suitable to identify biomarkers of CMT1A [65].…”
Section: Animal Models and Future Perspectivesmentioning
confidence: 99%